Metabolic Dysfunction Underlying Autism Spectrum Disorder and Potential Treatment Approaches - Cheng, Ning; Rho, Jong M.; Masino, Susan A. (Frontiers in Molecular Neuroscience, 2017)
Autism spectrum disorder (ASD) is characterized by deficits in sociability and communication, and increased repetitive and/or restrictive behaviours. The etio-pathogenesis is unknown, but overall, ASD has diverse clinical manifestations and has been associated with many possible genetic and environmental factors. As such, it has been a great challenge to identify key neurobiological mechanisms and to develop effective treatments. Current therapies focus on co-morbid conditions (such as epileptic seizures and sleep disturbances) and there is no cure for the core symptoms. Recent studies have increasingly implicated mitochondrial dysfunction. The fact that mitochondria are an integral part of diverse cellular functions and are susceptible to many insults could explain how a wide range of factors can contribute to a consistent behavioral phenotype in ASD. Meanwhile, the high-fat, low-carbohydrate ketogenic diet (KD), used for nearly a century to treat medically intractable epilepsy, has been shown to enhance mitochondrial function through a multiplicity of mechanisms, and to affect additional molecular targets that may address symptoms and comorbidities of ASD. Here, we delineate evidence for the use of metabolism-based therapies such as the KD in the treatment of ASD as well as emerging co-morbid models of epilepsy and autism. Future research directions aimed at validating such therapeutic approaches and identifying additional and novel mechanistic targets are also discussed.